2014
DOI: 10.1108/imr-02-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Does location matter to export performance?

Abstract: Purpose – The purpose of this paper is to build on the resource-based view to analyze the influence of location effects on a firm's ability to develop export-related resources and capabilities which then impacts on export performance. Design/methodology/approach – To test the proposed hypotheses, a sample of small-to-medium exporting firms located in Australia is analyzed using partial least squared modeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 149 publications
(215 reference statements)
1
69
2
Order By: Relevance
“…For the regions they researched, they found a positive influence of this factor. However, Freeman and Styles' (2014) research about Australian firms showed a neutral influence. This indicates that the factor adaptation of product strategy may have a positive influence in some regions and is relevant for German SMEs which target SSA.…”
Section: Multiple Regression Analysis With Dependent Factor Of Overalmentioning
confidence: 95%
See 2 more Smart Citations
“…For the regions they researched, they found a positive influence of this factor. However, Freeman and Styles' (2014) research about Australian firms showed a neutral influence. This indicates that the factor adaptation of product strategy may have a positive influence in some regions and is relevant for German SMEs which target SSA.…”
Section: Multiple Regression Analysis With Dependent Factor Of Overalmentioning
confidence: 95%
“…Consequently, multiple approaches are necessary to gain quantitative and qualitative data (Collis and Hussey 2014;Saunders 2012). Actually, many EP studies (e.g., Freeman and Styles 2014;Rambocas et al 2015) have applied this philosophy.…”
Section: Research Philosophymentioning
confidence: 99%
See 1 more Smart Citation
“…The following capabilities or capability dimensions from different studies could be classified under Cluster 1 (C1) as follows: (a) external collaboration (Lefebvre et al, 1998), (b) relational capability (Freeman and Styles, 2014;Lages et al, 2009;), (c) supplier and customer relationship capabilities (Kaleka, 2002), (d) communication capability (Zou et al, 2003), (e) relational-building capability (Morgan et al, 2004), (f) leveraging foreign distributer competences (Knight and Cavusgil, 2004), (g) alliance and network development capabilities (Freeman et al, 2006), (h) cooperation capability (Flor and Oltra, 2005), (i) networking capability (Bianchi, 2009;Chen et al, 2009;Raymond and St-Pierre, 2013;Van Geenhuizen, 2008;Weerawardena et al, 2007), (j) parental network capabilities (Elango and Pattnaik, 2007), (k) external communication as a sub-dimension of commercial capabilities (Camison and Villar, 2009), (l) meeting foreign customer demands and requests as dimensions of adaptive capability , (m) network capability upgrading , (n) marketing communication capability (Murray et al, 2011), (o) customer relation capability as the export marketing capabilities' dimension (Kaleka, 2011), (p) "building of sound and long-lasting relationships" as a sub-dimension of export-related organizational capabilities (Leonidou et al, 2011), (q) customer relationship capabilities as a component of dynamic marketing capabilities (Kaleka, 2012), (r) channel management and delivery management as a function of specialized marketing capabilities (Morgan et al, 2012), (s) alliance management capability (Khalid and Larimo, 2012), (t) channel networking capabilities (Boso et al, 2013), (u) listening to customers and scanning the business environment as components of dynamic capabilities (Al-Aali and Teece, 2014), (v) network learning capability (Weerawardena et al, 2014), and (w) distribution network as a function of marketing capability (Bortoluzzi et al, 2014).…”
Section: Cluster 1 (C1)-relational-based Fsamentioning
confidence: 99%
“…According to the business network and relational-based literature, there are different definitions as well as dimensions for NC provided by related researchers Mu and Benedetto, 2012;Ritter et al, 2002;Walter et al, 2006). As depicted in Table 2 (Freeman and Styles, 2014;Kaleka, 2012, Morgan et al, 2012Murray et al, 2011;Raymond and St-Pierre, 2013;Zou et al, 2003); (e) innovation (innovative) capability (Bianchi, 2009;Guan and Ma, 2003;Hortinha et al, 2011;Luo et al, 2005;Yi et al, 2012); (f) technological competence and unique product development (Knight and Cavusgil, 2004); (g) production capability as a component of technological capabilities (Flor and Oltra, 2005); (h) technological capability (Chen et al, 2009;Yiu et al, 2007); (i) innovation and technology capabilities as a sub-dimension of capability for internationalization (Camison and Villar, 2009 product innovation (Bortoluzzi et al, 2014) ; and (q) differentiation capability (Chen et al, 2014).…”
Section: Cluster 1 (C1)-relational-based Fsamentioning
confidence: 99%